As regras da TV Universitária: lutas para a constituição de um campo - Lima, Vilma Silva (2011)
The relations between the camps university / scientific and the television and the tensions that arose for the establishment of a television field are the subject of this university. The main objective of this work is based on the analysis of the university campus and field television - understand - the role played by TV at university overlap with those fields. Was taken as a paradigmatic example of the televisions that are part of the University Channel University of São Paulo (SP-CNU), the first university channel in the country to make use of theCable Law (8977) which in its Article 23 provides for free use of universities its area of service a television channel. The theoretical approach was in Bourdieu and the concepts of habitus and field his main references. The methodology included literature searches and field with four (4) agents(directors) of TV universities that participate in the CNU-SP